Nacella clypeater - González-Wevar, Claudio A.; Hüne, Mathias; Rosenfeld, Sebastián; Nakano, Tomoyuki; Saucède, Thomas; Spencer, Hamish; Poulin, Elie (Zenodo, 2018)
NACELLA CLYPEATER (LESSON, 1831) (FIG. 3) Patella clypeater Lesson, 1831: 419; Reeve, 1854: pl. 16, figs A, B; Huppé, 1854: 259. Nacella ( Patinella ) clypeater – Pilsbry, 1891: 122. Patinigera clypeata – Dell, 1964: 273. Nacella ( Patinigera ) clypeater – Powell, 1973: 193, pl. 175, figs 1, 2; Ramírez, 1981: 52; Valdovinos & Ruth, 2005: 504. Nacella clypeater – Aldea & Valdovinos, 2005: 369; González-Wevar et al. , 2010: 116; 2017: 863. Material studied: Coquimbo (29°58’04.68’’ S, 71°22’00.79’’W) N = 40; Valparaíso (33°00’56.98’’S, 71°33’39.62’’W) N = 25; Pichilemu (34°25’29.96’’S, 72°02’39.31’’W) N = 20; Tubul (37°13’11.09’’S, 73°26’35.55’’W) N = 35; Mehuín (39°26’39.04’’S, 73°13’52.63’’W) N = 25; La Misión (39°47’44.48’’S, 73°23’59.17’’W) N = 40; Pucatrihue (40°32’39.92’’S, 73°43’16.68’’W) N = 25. Shell: The shell shape and sculpture are relatively constant in the analysed individuals from different localities along the Chilean Central coast (Fig. 3A–F). The species exhibits a conical morphology, dorsally depressed with a relatively thick and non-translucent shell (Fig. 3A–C). The anterior part of the animal is laterally compressed (Fig. 3D–F). The shell is large (maximum length 120 mm) with a low profile. The apex is situated at the anterior 30% of the shell. The anterior slope of the shell is slightly concave, while the lateral and the posterior slopes are convex (Fig. 3A–C). The aperture of the shell is circular. The surface of the shell is sculptured with fine, rounded near-radial ribs and concentric growth lines beginning below the apex. The margin of the shell is relatively even. The external coloration varies (grey, green and brown) with clear white, yellow and creamy ribs. The internal part of the shell exhibits silvery to pale bronze, with a brown spot that corresponds to the impression of the body. External anatomy: The ventral area of the foot and the mantle fold are creamy white coloured and the epipodial fringe is recognizable. The mantle fold is thin and bordered by a black narrow line. Mantle tentacles are in alternate series of three short ones and a slightly longer one and lack pigmentation (Fig. 3G). The cephalic tentacles are not pigmented (Fig. 3G). Radula: See Valdovinos & Rüth (2005) (Fig. 3H). Distribution: Pacific margin of the Chilean coast between 42°S and 30°S (Fig. 3I). Habitat: Low intertidal and subtidal rocky shores between 0 to 20 m depths. Comments: Field observation along the Chilean coast shows that N. clypeater exhibits a patchy distribution being highly abundant in some localities and completely absent at others. In fact, Aguilera (2011), in a rocky intertidal trophic study across the Chilean coast, did not record the presence of N. clypeater and, therefore, considered it as an uncommon inter- subtidal species. Population-based analyses in the species suggest that N. clypeater represents a single genetic unit across its distribution and exhibits extremely low levels of mtDNA ( COI ) genetic diversity across its distribution (unpublished data). : Published as part of González-Wevar, Claudio A., Hüne, Mathias, Rosenfeld, Sebastián, Nakano, Tomoyuki, Saucède, Thomas, Spencer, Hamish & Poulin, Elie, 2019, Systematic revision of Nacella (Patellogastropoda: Nacellidae) based on a complete phylogeny of the genus, with the description of a new species from the southern tip of South America, pp. 303-336 in Zoological Journal of the Linnean Society 186 on page 309, DOI: 10.1093/zoolinnean/zly067, http://zenodo.org/record/5718878 : {"references": ["Reeve LA. 1854. Conchologia iconica: on illustrations of the shells of molluscous animals, Vol. VII. Heinietta Street, Covent Garden, London: Lovell Reeve.", "Huppe LH. 1854. Fauna Chilena. Molluscos. In: Gay C, ed. Historia Fisica y Politica de Chile. Zoologica, 8, Paris.", "Pilsbry HA. 1891. Manual of conchology. Structural and systematic with illustrations of the species, Vol. 13. Philadelphia, PA: Academy of Natural Sciences.", "Dell, RK. 1964. Marine Mollusca from Macquarie and Heard Islands. Records of the Dominion Museum 4: 267 - 301.", "Powell AWB. 1973. The patellid limpets of the World (Patellidae). In: Abbot RT ed. Indo-Pacific Mollusca: monographs of the marine mollusks of the world with emphasis on those of the tropical western Pacific and Indian Oceans, Vol. 3. Auckland, New Zealand: Auckland Institute and Museum.", "Ramirez J. 1981. Moluscos de Chile. Vol. 1 Archeogastropoda. Chile: Museo Nacional de Historia Natural. 1 \u00aa Edicion. Santiago, Chile.", "Valdovinos C, Ruth M. 2005. Nacellidae limpets of southern South America: taxonomy and distribution. Revista Chilena de Historia Natural 78: 497 - 517.", "Aldea C, Valdovinos C. 2005. Moluscos del intermareal rocoso del Centro-Sur de Chile (36 \u00b0 - 38 \u00b0 S): taxonomia y clave de indentificacion. Gayana 69: 364 - 396.", "Gonzalez-Wevar CA, Nakano T, Canete JI, Poulin E. 2010. Molecular phylogeny and historical biogeography of Nacella (Patellogastropoda: Nacellidae) in the Southern Ocean. Molecular Phylogenetics and Evolution 56: 115 - 124.", "Gonzalez-Wevar CA, Hune M, Segovia NI, Nakano T, Spencer HG, Chown S, Saucede T, Johnstone G, Mansilla A, Poulin E. 2017. Following the Antarctic Circumpolar Current: patterns and processes in the biogeography of the limpet Nacella (Mollusca: Patellogastropoda) across the Southern Ocean. Journal of Biogeography 44: 861 - 874.", "Aguilera MA. 2011. The functional roles of herbivores in the rocky intertidal systems in Chile: A review of food preferences and consumptive effects. Revista Chilena de Historia Natural 84: 241 - 261."]}